Capacity of middle management in health-care organizations for working with people—the case of Slovenian hospitals - Skela Savič, Brigita (BioMed Central, 2013)
BACKGROUND: Effective human resources management plays a vital role in the success of health-care sector reform. Leaders are selected for their clinical expertise and not their management skills, which is often the case at the middle-management level. The purpose of this study was to examine the situation in some fields that involve working with people in health-care organizations at middle-management level. METHODS: The study included eight state-owned hospitals in Slovenia. A cross-sectional study included 119 middle managers and 778 employees. Quota sampling was used for the subgroups. Structured survey questionnaires were administered to leaders and employees, each consisting of 24 statements in four content sets evaluated on a 5-point Likert-type scale. Respondents were also asked about the type and number of training or education programmes they had participated in over the last three years. Descriptive statistics, two-way analysis of variance, Pearson’s correlation coefficient and multiple linear regression were used. The study was conducted from March to December 2008. RESULTS: Statistically significant differences were established between leaders and employees in all content sets; no significant differences were found when comparing health-care providers and health-administration workers. Employment position was found to be a significant predictor for employee development (β = 0.273, P < 0.001), the leader–employee relationship (β = 0.291, P < 0.001) and organizational motivation (β = 0.258, P < 0.001). Area of work (β = 0.113, P = 0.010) and employment position (β = 0.389, P < 0.001) were significant predictors for personal involvement. Level of education correlated negatively with total scores for organizational motivation: respondents with a higher level of education were rated with a lower score (β = -0.117, P = 0.024). Health-care providers participate in management programmes less frequently than do health-administration workers. CONCLUSION: Employee participation in change-implementation processes was low, as was awareness of the importance of employee development. Education of employees in Slovenian hospitals for leadership roles is still not perceived as a necessary investment for improving work processes. Hospitals are state owned and a national strategy should be developed on how to improve leadership and management in Slovenian hospitals.